2017
DOI: 10.1021/acs.joc.7b01608
|View full text |Cite
|
Sign up to set email alerts
|

Hypervalent Iodonium Alkynyl Triflate Generated Phenylcyanocarbene and Its Reactivity with Aromatic Systems

Abstract: Phenylcyanocarbene was generated by the reaction of azide with a hypervalent iodonium alkynyl triflate and reacted in situ with 21 different carbocyclic and heterocyclic aromatic compounds. These reactions led to more complex products that frequently underwent subsequent rearrangements. The reactivity was further explored in a mechanistic study to ascertain the chemoselectivity and stereospecificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 47 publications
0
8
0
7
Order By: Relevance
“…In this work, all the norcaradiene-type products 3 are quite stable, and no cycloheptatriene was detected. In addition, norcaradiene has been reported to rearrange to the C–H insertion product in thermal, photochemical, or acid conditions . We have noticed that norcaradiene 3n was partially converted to the C–H insertion product 4n in the process of silica gel column chromatography purification .…”
Section: Resultsmentioning
confidence: 99%
“…In this work, all the norcaradiene-type products 3 are quite stable, and no cycloheptatriene was detected. In addition, norcaradiene has been reported to rearrange to the C–H insertion product in thermal, photochemical, or acid conditions . We have noticed that norcaradiene 3n was partially converted to the C–H insertion product 4n in the process of silica gel column chromatography purification .…”
Section: Resultsmentioning
confidence: 99%
“…In analogy to trapping experiments performed with cyanocarbenes, [16] electron-rich arenes were added to the reaction. Similar to reports for cyanocarbenes derived from alkynyliodoniumtriflates, [16] both pyrrole and 1,3dimethoxybenzene readily underwent the reaction to compounds 2 u and 2 v, with pyrrole being attacked in 2-position instead of at the nitrogen (Scheme 8A, 8B). The product formation can be explained through the addition of a cyanocarbene to the aromatic system and subsequent rearomatization in analogy to previous reports from Croatt et al [16] Next, styrene was added and the cyclopropane 2 x could be isolated as a 1 : 1 mixture of diastereomers (Scheme 8C).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, after UV irradiation, a signal was detected for both the pure alkynyl triazene and with PBN as a spin-trap. This could indicate both the presence of a triplet-type carbene [16,39] or an underlying radical mechanism. While all of the derived products indicate a carbene like mechanism, a parallel mechanism that is based on radicals at this stage cannot be excluded, hints for such type of side pathway come from another side product that can be explained in accordance with a radical path (dinitrile 6, see Supporting Information for further discussion).…”
Section: Methodsmentioning
confidence: 99%
“…Alkynyliodonium salts have been known to be highly electron‐deficient species and can serve as useful nucleophile acceptors for a range of nucleophiles, [2g,k,3a,11] including carbon atoms [11a–e] and heteroatoms [2g,k,3a,11f–u] . In particular, some research groups have reported that Michael addition reaction of alkynyliodonium derivatives using an azide group as the nucleophile proceeded efficiently and respective β‐azido vinyliodonium salts were obtained in good yields [11n,q,r] .…”
Section: Figurementioning
confidence: 99%